Penilaian Tingkat Kematangan Proses Pengelolaan Proyek Dalam Project NCX (New Customer Xperience) Menggunakan CMMI - ACQ (Studi Kasus: PT XYZ) - Rahmi Maulidya; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT XYZ is a company that engaged in network and telecommunication service in Indonesia. PT XYZ requires a CRM solution that is able to support a variety business. To achieve that, PT XYZ made a project called project NCX (New Customer Xperience), which is an acquisition project to replace the old CRM strategy to the new one, This research aims to do an assessment in project NCX by using CMMI (Capability Maturity Model Integration). Using a qualitative method, the assessment run with SCAMPI class C (Standard Appraissal Method for Process Improvement). Assessment is selected at maturity level two which contains of nine process area. Results of maturity level two assessment found that only three area processes were fulfilled and at level two or managed, were measurement and analysis, process and product quality assurance, solicitation and supplier agreement development. From the results of assessment, a gap analysis was conducted to measure the area process gap with assessment target, then make recommendations for the company regarding the weaknesses found in the product development process based on CMMI.